Trade, Technology and Labour Markets - Empirical Controversies in the Light of the Jones Model - Michael Pflüger (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
The deterioration of the income and employment position of unskilled workers in the OECD since the 1980s is a well-documented fact. The debate about the causes of this development is dominated by two competing hypotheses, "North-South Trade" ("globalisation") and technological progress. Several empirical methodologies have been used to identify and quantify the importance of these two explanations: factor content analyses, consistency checks, regression analyses and numerical methods. However, no consensus has been achieved so far and there is considerable methodological controversy. This paper uses Jones?s (1965) exposition of the standard trade model as analytical backbone to identify and settle the sources of disagreement, to provide a synthesis of existing results, to derive new insights, and to provide a comprehensive assessment of the aforementioned empirical methodologies.
Keywords: J31; F21; F16; 330; North-South Trade; Technology; Wage Inequality; Unemployment; Globalisierung; Nord-Süd-Beziehungen; Technischer Fortschritt; Beschäftigungseffekt; Ungelernte Arbeitskräfte; Faktorproportionentheorem; Allgemeines Gleichgewicht; Mehr-Sektoren-Modell; Lohnstruktur; Theorie